Crop residue management for productivity enhancement and sustainability under various cropping systems– A Review - GUPTA, VIKAS; SHARMA, B. C.; SINGH, MAHENDER; GUPTA, MEENAKSHI; SHARMA, RAKESH (Journal of Soil and Water Conservation, 2018)
A huge volume of crop residues are produced both on-farm and off-farm. These crop residues are used for animal feeding, soil mulching, bio-manure making, thatching for rural homes and fuel for domestic and industrial use. Thus crop residues are of tremendous value to the farmers. However, a large portion of the residues is burnt on-farm primarily to clear the field for sowing of the succeeding crop. The problem of on-farm burning of crop residues is intensifying in recent years due to shortage of human labour, high cost of removing the crop residues by conventional methods and use of combines for harvesting of crops. The residues of rice, wheat, cotton, maize, millet, sugarcane, jute, rapeseed-mustard and groundnut are typically burnt on-farm across different states of the country. The problem is more severe in the irrigated agriculture, particularly in the mechanized rice-wheat system of the northwest India. Modern agriculture is now at the crossroads ecologically, economically, technologically and socially due to soil degradation. Critical analysis of available information showed that problems of degradation of soil health are caused due to imbalanced, inadequate and pro-macronutrient fertilizer use, inadequate use or no use of organic manures and crop residues and less use of good quality biofertilizers. Although a massive amount of crop residues and manure is produced in farms, it is becoming increasingly complex to recycle nutrients, even within agricultural systems. Therefore, there is a need to use all available sources of nutrients to maintain the productivity and fertility at a required level. Among the available organic sources of plant nutrients, crop residue is one of the most important sources for supplying nutrients to the crop and for improving soil health. The main goals of agriculture like maintenance of highly productive cropping, protection of soils against erosion, conservation of organic matter, provision of optimum conditions for soil biota, to prevent undesirable effects of high-level fertilizer applications, the highest possible rate of recycling of plant nutrients could easily be fulfilled through appropriate field management of crop residues.